Evaluation of a PlayPosit guided group project's impact on student engagement in an undergraduate course - Dasantila Sherifi; Yuane Jia; Thomas J. Hunt; Memory Ndanga (Springer, 2023)
Abstract Student engagement is critical for meaningful learning and can be impacted by teaching methods, tools, and course content. Online student engagement continues to be challenging because online classes offer fewer ways to engage with professors, peers, and the university than in-person classes. PlayPosit is a video teaching tool that incorporates questions to check for understanding. Our study aimed to evaluate how a PlayPosit guided group project impacted engagement in a structured online learning environment. For this qualitative study, a PlayPosit guided group project was implemented in an online undergraduate course taught via Canvas learning management system. Engagement was evaluated using online course analytics and student's written feedback. Canvas reports were analyzed using descriptive statistics, and students' written feedback was analyzed using directed content analysis. All 29 students enrolled in the course completed the course successfully. They completed 99.3% of the PlayPosit activities with accuracy 87.6-100% and completed the course project with scores 89-100%. Student comments were grouped into themes related to PlayPosit, group project, and engagement. Students found PlayPosit activities helpful/beneficial, aligned with deliverables, a great learning resource, and enjoyable. Students recognized the group project for its importance in teaching them collaboration, expressed that it enabled them to learn more from each-other, was an enjoyable networking experience, and was challenging. Engagement themes included knowledge gained was applicable to the real world, the course stimulated higher-order thinking, and the course was enjoyable and kept students wanting more. This study suggested that a PlayPosit guided group project was well-received by students and contributed to high engagement with the content, peers, and the professor.